Effectiveness Microkapsul Feed Enriched Maggot Flour (Hermetia Illucens) on the Growth of Saline Tilapia (Oreochromis Niloticus) to Increase People's Income - Soeprapto, Hayati; Madusari, Beny Diah; Fataray, Andi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The purpose of the study was to determine the growth of saline tilapia fed artificial feed in the form of microcapsules enriched with protein in the form of magot flour, which has a standard composition for fish growth in general. The research method used was a completely randomized design with 4 treatments and 3 replications. In this study, the time intervals for treatment were: A (feeding every 2 hours), B (feeding every 4 hours), C (feeding every 6 hours), D (feeding every 8 hours). The results showed that the highest average growth was obtained in treatment B with an interval of 4 hours, the increase in biomass reached 11.57 grams. While the lowest growth was obtained in treatment D at an interval of 8 hours resulting in an average growth of 3.56 grams. The results of the analysis of variance on the growth of saline tilapia biomass showed that the calculated F value was greater than the F table 1% and 5%. This shows that artificial microcapsule feed can be consumed quite well, on a laboratory scale. This was also proven in the Tukay test which showed a difference in the effect of microcapsule feed given at different time intervals. In addition, there are supporters in the maintenance of the research, namely water quality, including temperature during the study between 270C – 290C, water pH ranging from 6.5 - 9, and water salinity during the study between 0 - 30 ppt.